2016
DOI: 10.1002/ejoc.201600947
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluoroalkyl Pyrazoles from In‐Situ‐Generated C2F5CHN2 and Electron‐Deficient Alkenes

Abstract: C2F5‐substituted pyrazolines were synthesized by [3+2]‐cycloaddition between in‐situ‐generated C2F5CHN2 and electron‐deficient alkenes. The addition of DBU led to the elimination of HF to give CF3CHF‐substituted pyrazoles. Depending on the structure of the pyrazolines, different products were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…In 2014, following the original protocol of Morandi and Carreira, our group generated CF 3 CHN 2 ( 1 ) in situ by stirring a mixture of sodium nitrite and trifluoroethylamine hydrochloride ( 2 *HCl) in a biphase mixture of dichloromethane/water at 0 °C. , Adding an alkene to the reaction mixture allowed obtaining mono- and disubstituted pyrazolines 44 – 49 in excellent yields (Scheme ). The whole sequence was performed in an operationally simple “one-flask” manner.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…In 2014, following the original protocol of Morandi and Carreira, our group generated CF 3 CHN 2 ( 1 ) in situ by stirring a mixture of sodium nitrite and trifluoroethylamine hydrochloride ( 2 *HCl) in a biphase mixture of dichloromethane/water at 0 °C. , Adding an alkene to the reaction mixture allowed obtaining mono- and disubstituted pyrazolines 44 – 49 in excellent yields (Scheme ). The whole sequence was performed in an operationally simple “one-flask” manner.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…In 2004, Yuan and co-workers revealed the cycloaddition of the Rh-carbenoids derived from the OBR with the arylnitriles resulting in the synthesis of oxazolyl-4-phosphonates . The recent seminal contributions from the Namboothiri, Smietana, and Mohanan groups have revealed that the intermediate (diazomethyl)­phosphonate anion can be efficiently trapped in an apparent (3 + 2)-cycloaddition process with conjugated olefins, imines, and alkynes resulting in the formation of pyrazolyl-/triazolylphosphonates . The presence of the pyrazole unit in various marketed drugs and the easy introduction of the phosphonate group has led to rapid exploration of this area .…”
mentioning
confidence: 99%
“…Having looked at the available information on the reactions employing OBR, it was apparent that all reports comprise of the selective loss of either the acyl or the azo groups, with the phosphonate group carried forward in the end products . However, retaining the acyl group in place of phosphonate is an attractive proposal that provides more substituent diversity and a provision for further functionalization.…”
mentioning
confidence: 99%
“…In 2015, during the course of our ongoing project on diazoalkanes, we developed a novel chemical reagent – difluoromethyldiazomethane, CF 2 HCHN 2 ( 1 ) . We first studied its reaction with alkynes towards CHF 2 ‐pyrazoles .…”
Section: Resultsmentioning
confidence: 99%